Gallbladder Clear Cell Carcinoma: Report of a Rare Case and Literature Review - Panayiotis Papatheodorou; Kyriakos Frantzeskou; Kyriaki Konstantinou; Elena Theophanous (Case Reports in Surgery)
Carcinoma of the gallbladder is the most common biliary tract cancer. The majority of gallbladder cancers are adenocarcinomas, whereas clear-cell carcinoma of the gallbladder (CCG) is a rarely recorded variant. Usually, diagnosis is established incidentally after cholecystectomy, performed for another reason. Clinically, the different histological types of carcinomas are impossible to be recognized preoperatively, since they present with a wide and common range of symptoms. We present a male patient who underwent an emergency cholecystectomy due to suspected perforation. After an uneventful postoperative period, the histopathological report led to the diagnosis of CCG, but the surgical margins were infiltrated by the tumor. The patient decided not to proceed with any additional treatment and passed away 8 months after the operation. In conclusion, it is of great necessity to record such unusual cases and enriches global knowledge with information clinically and educationally noteworthy.